Historical and cultural analysis of the development of Philippine dress - Rodriguez, Rochelle Ann S. (UP College of Home Economics, 2012)
The study is a historical analysis of the development of Philippine dress and how it reflected Philippine cultural values and national identity. The periods covered in the study started from the arrival of the Spanish (16th century) to the Estrada administration (1999). It focused on the changes in the Philippine dress such as accessories, garment details, silhouette, and materials. These changes were related to the historical context, specifically socio-economic, technological, and political environments. These changes were compared to the changes in the western dress and analyzed through fashion adoption theories. Information on the changes in costume per period were taken from primary sources such as museum exhibits and magazines. History books were also used to understand he changes in the costume and to identify the significant historic events. The study found that Filipino women only adopted fashion innovations that were practical, modest, feminine, and that some details cannot be directly traced to western influence. The study concluded that the development of Philippine dress reflected a acculturated nation. Despite western influence, the original values f Filipino women were preserved. The researcher recommends to incorporate the results of the study in courses related to the development of Philippine and Asian costumes to make the students realize they should look into their own cultural values instead of aiming only to emulate western fashion.